Variation and changes in soccer players’ names of Brazilian National soccer team-TRAD- - Pereira de Souza Cruz, Vinícius; Roque Amaral, Eduardo Tadeu (Onomástica desde América Latina, 2020)
This paper presents an analysis of official and unofficial anthroponyms of soccer players from the Brazilian National team from 1958 to 2018. The theoretical framework is based on both onomastic studies, such as Amaral (2011), Amaral e Seide (2020), Bajo Pérez (2002), Becker (2012), Fernández Leborans (1999), Urrutia and Sánchez (2009), Van Langendonck (2007), Fernández Leborans (1999) and on analyses about Brazilian soccer studies such as Rodrigues (2010) and Caetano and Rodrigues (2009). The data analyzed are the players’ names on the lists selected to compete World Cup in that period. These names are classified in order to observe variation and change over time. The results indicate a predominance of official names in almost every year as well as a greater contemporary trend towards more formal name variants.